Helical Antimicrobial Peptide Foldamers Containing Non‐proteinogenic Amino Acids - Yokoo, Hidetomo; Hirano, Motoharu; Misawa, Takashi; Demizu, Yosuke (ChemMedChem, 2021)
Antimicrobial peptides (AMPs) are potential novel therapeutic drugs against microbial infections. Most AMPs function by disrupting microbial membranes because of their amphipathic properties and ordered secondary structures. In this minireview, we describe recent efforts to develop helical AMP foldamers containing non‐proteinogenic amino acids, such as α,α‐disubstituted α‐amino acids, β‐amino acids, γ‐amino acids, side‐chain stapling and N‐alkyl glycines. Developing peptides with superior potencies: In this minireview, we focus on helix‐stabilized peptide foldamers with antimicrobial activity and describe their components, secondary structures, antimicrobial activity and utility. We describe recent developments in foldamers containing non‐proteinogenic amino acids that exhibit high antimicrobial activity and increased resistance to proteases, and how the use of such amino acids can increase selectivity.